IMPROVING THE QUALITY OF MADRASAH IBTIDAIYAH THROUGH RELIGIOUS MODERATION APPROACH: A STUDY OF BASIC EDUCATION LITERATURE IN INDONESIA - Syaifudin Zuhri (MEDIA DAN STRATEGI PEMBELAJARAN, 2025)
Elementary School (MI) as an Islamic-based basic education institution in Indonesia has a strategic role in shaping a quality generation, both in terms of academics and character. However, challenges such as low quality of education, lack of innovation, and potential radicalism demand relevant quality improvement strategies. The religious moderation approach emerges as a promising solution to improve the quality of MI through strengthening tolerance, inclusiveness and balance in religious education. This article aims to review the literature related to improving the quality of MI through a religious moderation approach, with a focus on the concept, implementation and impact on basic education in Indonesia. The literature study method is used by analysing Scopus indexed journals, SINTA, and supporting books. The results show that religious moderation can improve the quality of Elementary School MI through an inclusive curriculum, contextual learning methods, and the role of teachers as role models.